Pembelajaran Berbasis Lingkungan dalam Islam: Sebuah Tinjauan Filosofis - Songyanan, Afifudin; Nur Arfiyah (Lembaga Intelektual Muda (LIM) Maluku, 2026)
This study explores environment-based learning from an Islamic philosophical perspective. The main objective of this scholarly work is to uncover the ontological, epistemological, and axiological foundations of environmental education grounded in the values of the Qur’an and the Islamic intellectual tradition. Employing a philosophical literature review approach, this study examines key concepts such as khalīfah (human stewardship over the earth), mīzān (balance), the prohibition of isrāf (extravagance), and amanah (trust and responsibility). The findings reveal that environment-based learning in Islam is not merely pragmatic but deeply rooted in theological awareness and spiritual ethics. Islamic environmental education aims to cultivate ecological character, foster moral responsibility, and encourage sustainable behavior as an expression of servitude to Allah SWT. This study recommends the integration of Islamic values into curricula, teaching methods, and assessment systems in Islamic educational institutions to develop a holistic and sustainability-oriented educational paradigm.